The Tempe Juice And Yogurt's Efficacy On Pregnancy Hypertension - Endah Yulianingsih; Sri Sujawatty; Yollanda Dwi Santi Violentina; Nurfaizah Alza; Ika Suherlin; Rahman Suleman; Miranie Safaringga; Rahma Dewi Agustini (Window of Health : Jurnal Kesehatan, 2025)
Hypertension is one of the non-communicable diseases that causes most deaths. In the last six months, there have been ten cases of hypertension in pregnant mothers in the South City Health Center. Age, genetic factors, and parity can cause hypertension in pregnant mothers. This study aims to determine whether tempe yogurt and tempe spice juice help reduce hypertension in pregnancies in the South Puskesmas Working Region. The quantitative study was conducted from April to September 2023 and used a quasi-experimental design of two groups of pretest and posttest. A purposive sampling of forty individuals was used to collect the samples. The results of the study showed that respondents in group A were over 35 years old (35%), group B was 20-35 years old (45%), and group A had a parity of between 2 and 4 years (55%), and group B had a Parity of 2 to 4 years (80%). No history of hypertension in groups A and B (75%, 70%). It can be concluded that consuming tempe yogurt and tempe spice juice regularly is shown as one way to reduce hypertension during pregnancy.